Integrated Corporate Governance Moderates Determinants On Economic Performance - Qintharah, Yuha Nadhirah; Murwaningsari, Etty; Rachmawati, Sistya (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: This study aims to examine the effect of corporate social responsibility and competitive advantage on economic performance in addition to using integrated corporate governance as a moderating variable. Thus, this study also aims to determine whether integrated corporate governance strengthens or weakens the relationship.Methodology: The research method used is moderated regression analysis (MRA). Data used in this research is secondary data from IDX. In addition, this study tested the classical assumptions and tested the accuracy of the model to find out which model was the most appropriate. The number of samples used in this study was 201 samples from the annual year 2020-2022.Finding: The results show that CSR does not affect economic performance, competitive advantage has a positive effect on economic performance, CG strengthens the influence of CSR on economic performance and CG strengthens the influence of competitive advantage on economic performance.Conclusion: Governance is an important factor in company performance because it can moderate the relationship between competitive advantage and CSR with performance. This research indicates the importance of competitive advantage to improve company performance. This is supported by the RBV theory which states to make good use of company resources. Also, governance could become quasi-moderation because it could become a moderator variable and could influence an independent variable.Novelty: This research uses different measurements of integrated corporate governance measurement. ICG measurement in this research is using developed POJK no 2/POJK 05/2014 indicators.